Structure and Properties of a cis-1, 4-Polybutadiene/Organic Montmorillonite Nanocomposite Prepared via In Situ Polymerization. Issue 7 (3rd July 2017) - Hua, Jing; Liu, Jinhui; Wang, Xin; Yue, Ziyu; Yang, Haida; Geng, Jieting; Ding, An
ABSTRACT: Cis-1, 4-polybutadiene (cis-1, 4-PB) is one of the most important synthetic rubbers, having superior performances such as wear resistance, cold resistance and high elasticity. However, its mechanical properties, including low tensile strength, tear resistance and thermal stability, limit its application in comparison to natural rubber and butadiene-styrene rubber that have excellent overall performances. Thus, the reinforcing of cis-1, 4-PB is a necessity. The dispersion of clay in rubbers on the nanoscale can improve the mechanical, gas permeability and thermal properties of the resulting composites. In this paper, organic montmorillonite (OMMT) clay was dispersed into the cis-1, 4-PB matrix via an in-situ polymerization method and the chemical structure, phase morphology, mechanical properties and thermal stability of the composite were investigated. The properties of the composite were analyzed by such techniques as X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), transmission electron microscopy (TEM) and thermal gravimetric analysis (TGA). In the in-situ polymerization, a Ni-based catalyst system with the presence of OMMT showed high efficiency and 1, 4-selectivity for the polymerization of butadiene. The OMMT could be dispersed in the polymeric matrix on the nanoscale during the polymerization. The interfusion of OMMT had little influence on the thermal stability and the chemical micro-structure of the cis-1, 4-PB when the content of cis-1, 4 units was more than 95%. The loss tangent of the composite was higher than that of cis-1, 4-PB from −110 to −55°C, the temperature range examined, and the mechanical properties of the cis-1, 4-PB/OMMT nanocomposite (NC) were improved upon the addition of OMMT.